Diagnosis and Management of Pediatric Diseases - Sergi, Consolato (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
A screenshot of some the most rapidly evolving fields in Neonatology and Pediatrics with articles reviewing some metabolic dysregulations as well as non-oncologic diseases that may occur in infancy, childhood, youth. The illustrative material with original photographs and drawings highlighting some pathogenetic concepts are keystones of this book.